Selected Genetic Characteristics of the Vietnamese Minority Living in the Czech Republic - Pham, Khanh Ha; Hubáček, Jaroslav A (Folia biologica, 2025)
The aim of this study was to analyse the allelic distribution of selected genes in the Czech and Vietnamese populations. We analysed samples from 94 Vietnamese volunteers and 2,859 Czech population-based subjects (2,559 from the Czechs post-MONICA and 300 volunteers from the South region of the Czech Republic). There were significant differences between the two populations for most, but not all, of the SNPs analysed. In particular, the prevalence of risk alleles in the analysed polymorphisms tended to be lower in the Vietnamese community compared to the Czech population, especially within the FTO (rs17817449; associated with obesity risk, P < 0.0001), TCF7L2 (rs7903146; linked to type 2 dia-betes, P < 0.0001) and ADH1B (rs1229984; related to alcohol consumption, P < 0.0001) genes. The genotype within the MCM6/LCT cluster (rs4988235) associated with lactase persistence was not present in the Vietnamese population. Slight genotype differences were detected for one HFE polymorphism (rs1799945 with P = 0.005; but not for rs1800562). Only the genotype frequencies within the MC4R and APOE genes were almost identical in both populations. We conclude that the Vietnamese population may have a lower genetic predisposition to the non-communicable diseases such as obesity or diabetes mellitus.
Keywords: dospělí; Genotype; Female; Minority Groups; obyvatelé jihovýchodní Asie; menšiny; Adult; ženské pohlaví; jednonukleotidový polymorfismus; Gene Frequency; lidé; Polymorphism, Single Nucleotide; genotyp; nutrigenetics; Southeast Asian People; Vietnam; frekvence genu; SNP; Male; Czech Republic; genetic analysis; nutrition; Česká republika; lidé středního věku; mužské pohlaví; Middle Aged; interethnic analysis; Humans